Franz Xaver Wolfgang Mozart (1791−1844), Johann Gallus Mederitsch (1752−1835) i nowy katalog ich zbiorów muzycznych - Neumayr, Eva (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2023)
Franz Xaver Wolfgang Mozart (1791−1844), Wolfgang Amadé and Constanze Mozart’s youngest son, as a pianist, composer and conductor was active in and around Lviv from 1809 to the end of the 1830s. When he died in 1844, his universal heiress Josephine Baroni-Cavalcabò donated his large music collection containing many letters and autographs of the Mozart family to the Dommusikverein and Mozarteum, a society that had been founded in Salzburg in 1842. Later, the society also acquired the music collection of his older brother Carl Thomas. Apart from the work of Franz Xaver Wolfgang Mozart, the collections comprise a large number of the original letters of the Mozart family, several autograph copies of the father's works and some of his instruments. The musical sources were catalogued in the RISM-database and a printed catalogue has been published.